2017
DOI: 10.1002/smll.201702853
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Interlayer Based on Molybdenum Diphosphide Catalyst and Carbon Nanotube Film for Lithium–Sulfur Batteries

Abstract: A multifunctional interlayer, composed of molybdenum diphosphide (MoP ) nanoparticles and a carbon nanotube (CNT) film, is introduced into a lithium-sulfur (Li-S) battery system to suppress polysulfide migration. Molybdenum diphosphide acts as the catalyst and can capture polysulfides and improve the polysulfide conversion activity during the discharge/charge processes. The CNT film acts as a conductive skeleton to support the MoP nanoparticles and to ensure their uniform distribution. The CNT film physically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
97
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(98 citation statements)
references
References 42 publications
1
97
0
Order By: Relevance
“…[35] In Ta ble 1, we compare the electrochemical performance of our fabricated cell to those reported in the literature. [32][33][34][35][36][37][38][39][40][41][42][43] Our NSCNTs/MoS 2 /S-NM cell presents outstanding cycling performance and high sulfur utilization.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…[35] In Ta ble 1, we compare the electrochemical performance of our fabricated cell to those reported in the literature. [32][33][34][35][36][37][38][39][40][41][42][43] Our NSCNTs/MoS 2 /S-NM cell presents outstanding cycling performance and high sulfur utilization.…”
Section: Resultsmentioning
confidence: 94%
“…In another study, a specific capacity of 660 mAh g −1 (sulfur loading of 1.5 mg cm −2 , after 250 cycles at 1.0 C) was achieved by the incorporation of nitrogen, carbon, and cobalt in a metal–organic‐framework‐derived porous interlayer . In Table , we compare the electrochemical performance of our fabricated cell to those reported in the literature . Our NSCNTs/MoS 2 /S‐NM cell presents outstanding cycling performance and high sulfur utilization.…”
Section: Resultsmentioning
confidence: 99%
“…It is mentionable that CNTs with conductive framework can ensure fast charge transport and reduce additional surface diffusing step, which can also enhance the reaction kinetics. The MoP 2 /CNT interlayer exhibited a reversible specific capacity of 905 mAh g −1 over 100 cycles at 0.2 C. [67] Currently, Liu and co-workers reported a strategy of P-doped carbon-coated CNT matrix combined with Ni 3 P nanospheres (PCCNT@NPS) as a multifunction interlayer. Kuang et al reported 1 nm thin Fe 3 C nanosheet anchoring on mesoporous carbon (Fe 3 C-MC) to serve as the host of Li-S battery.…”
Section: Adsorption-catalysis Synergymentioning
confidence: 99%
“…In this design, the CNT film severed as a current collector to hinder LiPSs migration and provided pathways for electron transfer, the MoP 2 nanoparticles acted as the catalyst to accelerate the conversion reaction, which can enhance the reaction kinetics. The MoP 2 /CNT interlayer exhibited a reversible specific capacity of 905 mAh g −1 over 100 cycles at 0.2 C. [67] Currently, Liu and co-workers reported a strategy of P-doped carbon-coated CNT matrix combined with Ni 3 P nanospheres (PCCNT@NPS) as a multifunction interlayer. With the abundant chemical adsorption, the strong physical adsorption and efficient catalytic ability, the battery delivered a high initial discharge capacity of 1067 mAh g −1 with a low capacity degradation of 0.077% per cycle over 500 cycles at 1 C. [68]…”
Section: Adsorption-catalysis Synergymentioning
confidence: 99%
“…With the development of advanced portable electronic devices and zero-emission electric vehicles, the demand for batteries with long cycle life, high capacity, and low self-discharge is continuously increasing. [1][2][3][4] Sony for the first time commercialized lithium-ion batteries (LIBs) in the early 1990s. 5 Thereafter, LIBs have been racing ahead during the past decades as the power source of choice.…”
Section: Introductionmentioning
confidence: 99%